Effect of ultrasound assisted cleaning on pesticide removal and quality characteristics of Vitis vinifera leaves - Alev Yüksel Aydar; Tuba Aydın; Alican Karaiz; Furkan Alabey; Anjineyulu Kothakota; António Raposo; Najla Abdullah Albaridi; R. Pandiselvam (Ultrasonics Sonochemistry, 2023)
In this study, the pesticide (acetamiprid, deltamethrin, and pyridaben) removal and physicochemical quality improvement of vine (Vitis vinifera) leaf were examined using ultrasonic and traditional cleaning for 5, 10, and 15 min. After an ultrasonic cleaning procedure at 37 kHz for 10 min, acetamiprid, deltamethrin, and pyridaben in vine leaf were reduced by 54.76, 58.22, and 54.55 %, respectively. Furthermore, the total phenolic content (TPC) in vine leaf increased to 13.45 mg GAE/g DW compared to that in control samples using traditional cleaning (10.37 mg GAE/g DW), but there were no significant differences in DPPH radical scavenging activity. After 15 min of conventional cleaning, the total chlorophyll and total carotenoid content of leaves were found to be lowest among all samples, at 6.52 mg/kg and 0.48 mg/kg, respectively. In conclusion, when compared to conventional cleaning methods, ultrasonic cleaning with no chemicals or heat treatment has proven to be a successful and environmentally friendly application in reducing commonly used pesticides and improving the physicochemical qualities of leaves.